The development of Kosovo and its relationship with the EU - Novitet Xh. Nezaj (Europa-Kolleg Hamburg, Institute for European Integration, 2015)
Kosovo used to be part of post-communist Yugoslavia. After the war in 1999, Kosovo has experienced an enormous political and economic transformation. This transformation has been assisted by the European Union. This paper aims to highlight the historical background of Kosovo, specific aspects of the relationship between the EU and Kosovo over the course of history, the EU's financial assistance, and the impact of this assistance on Kosovo's economic development from 1999 onwards. Furthermore, it includes an overview of the framework of cooperation and the recent underlying dynamics up to 2014, as well as the prospects for the future relationship between the EU and Kosovo. This paper has a persuasive argument to make, to defend the need to uphold the system of law and to adapt it to the changing needs brought about by the new realities of European integration.
Keywords: 320; European integration; pre-accession; UN; reconstruction; SAA; accession; EU law; financial assistance; approximation